2019
DOI: 10.3390/md17110628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astaxanthin from Shrimp Shell on Oxidative Stress and Behavior in Animal Model of Alzheimer’s Disease

Abstract: This study aimed to investigate the effect of astaxanthin (ASX) extracted and ASX powder from shrimp (Litopenaeus vannamei) shells on Wistar rats with Alzheimer’s disease, induced by amyloid-β (1-42) peptides. In this task, the rats were divided into eight groups: (1) Control, (2) sham operate, (3) negative control (vehicle) + Aβ1-42, (4) ASX extract+Aβ1-42, (5) commercial ASX + Aβ1-42, (6) ASX powder + Aβ1-42, (7) blank powder + Aβ1-42, and (8) vitamin E + Aβ1-42. All treatments were orally administrated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
(44 reference statements)
2
40
0
Order By: Relevance
“…Dietary supplementation of PC improved cognitive function by inhibition of oxidative stress and Aβ-induced neurotoxicity [ 25 , 26 ]. The administration of astaxantin, which is an active component of KO, improved cognitive and memory function by inhibition of oxidative stress and Aβ plaque level in an Aβ-treated rat model [ 27 ]. However, the cognitive improvement effects and its mechanisms of KO, which is rich sources of PUFAs, PC, and astaxantin, against Aβ 25–35 -induced cognitive impairment have not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation of PC improved cognitive function by inhibition of oxidative stress and Aβ-induced neurotoxicity [ 25 , 26 ]. The administration of astaxantin, which is an active component of KO, improved cognitive and memory function by inhibition of oxidative stress and Aβ plaque level in an Aβ-treated rat model [ 27 ]. However, the cognitive improvement effects and its mechanisms of KO, which is rich sources of PUFAs, PC, and astaxantin, against Aβ 25–35 -induced cognitive impairment have not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin is able to act against Alzheimer’s disease. In Wistar rats with Alzheimer’s disease, astaxanthin powder from shrimp ( Litopenaeus vannamei ) shells showed a significant alleviation of cognitive functions ( Table 1 ) [ 48 ]. In APP/PSEN1 (APP/PS1) double-transgenic mice, the administration of synthesized docosahexaenoic-acid-acylated astaxanthin diesters (AST-DHA) attenuated cognitive disorders by regulating the parameters of oxidative stress and suppressing neuroinflammation ( Table 1 ) [ 49 ].…”
Section: The Anti-inflammatory Effects Of Astaxanthin In Chronic Amentioning
confidence: 99%
“…Previous studies have demonstrated the potential effective role that ASX might have in the management of AD. A previous study by Taksima et al [ 47 ], where the authors used ASX powder obtained from shrimp shells ( Litopenaeus vannamei ), showed that Wistar rats with AD had significantly improved levels of their cognitive abilities. ASX has significantly enhanced spatial and non-spatial memory and reduced neurodegeneration, assessed by the object recognition test and Aβ plaque level [ 47 ].…”
Section: Astaxanthin For Neurological Disordersmentioning
confidence: 99%
“…A previous study by Taksima et al [ 47 ], where the authors used ASX powder obtained from shrimp shells ( Litopenaeus vannamei ), showed that Wistar rats with AD had significantly improved levels of their cognitive abilities. ASX has significantly enhanced spatial and non-spatial memory and reduced neurodegeneration, assessed by the object recognition test and Aβ plaque level [ 47 ]. It was thought that ASX might improve GPx activity, which was observed to be suppressed due to mitochondrial dysfunction and Aβ accumulation [ 47 , 48 ].…”
Section: Astaxanthin For Neurological Disordersmentioning
confidence: 99%